Identifikasi Penyebab Kerusakan Mesin Pompa pada Sistem Distribusi Air PDAM Menggunakan FMEA dan LTA - Irawan, Heri Tri; Pamungkas, Iing; Akmal, Abdiel Khaleil; Pandria, T.M. Azis; Sofiyanurriyanti, Sofiyanurriyanti; Hasnita, Hasnita; Azhar, Azhar (Jurnal Optimalisasi, 2024)
The existence of a Regional Drinking Water Company (PDAM) is very important in maintaining the continuity of the clean water treatment process running smoothly and well. Maintenance of clean water distribution machines and equipment is a matter that requires attention because damage to one of the machines or equipment can cause a cessation of processing activities which results in losses for companies and services. Damage to the water distribution machine in PDAM Tirta Mountala is unavoidable and this happens frequently. This happens because the damage is not properly identified, either in preventive maintenance or in anticipating appropriate action. The purpose of this study is to identify the cause of the damage and propose maintenance actions on the clean water distribution pump machine in PDAM Tirta Montala Aceh Besar. The failure mode and effect analysis (FMEA) and logic tree analysis (LTA) approaches are used to anticipate this. FMEA is an approach used to identify and analyze potential failures and their consequences. Meanwhile, LTA aims to prioritize each damage mode and carry out reviews and functions, malfunctions so that the damage mode status is not the same. There are eighteen water distribution pump components with the highest damage frequency. Based on the results of the FMEA, five components with the highest RPN or the highest risk were obtained, namely the vane, stuffing box, bearing bracket support, shaft and bearing components. The five components were then analyzed through LTA and maintenance tasks with several proposed actions including repair, component replacement, welding, thermography, and re-measurement with a vibration meter.